Reflecţii asupra jurisprudenţei curţii constituţionale privind dreptul la un nivel de trai decent [Articol] - Sandu, Victor (CEP USM, 2023)
The rule of law and democracy implies the constitutional guarantee of citizens’ fundamental rights and freedoms as supreme values. This guarantee must be ensured by the state institutions, implicitly by the Constitutional Court which guarantees the supremacy of the Constitution, which reflects the fundamental law of the expression of the sovereignity of the people. In this article we will elucidate this constitutionally determined function through the prism of guaranteeing the right to a decent standard of living, within the jurisprudence of the Constitutional Court.

Statul de drept și democratic implică garantarea constituțională a drepturilor și libertăților fundamentale ale cetățeanului ca valori supreme. Această garanție trebuie asigurată de către instituțiile statului, implicit de către Curtea Constituțională care garantează supremația Constituției, Legea fundamentală a expresiei voinței suverane a poporului. În comunicarea dată vom elucida această funcție determinată constituțional prin prisma garantării dreptului la un nivel de trai decent, în jurisprudența Curții Constituționale.
REFLECTIONS ON THE JURISPRUDENCE OF THE CONSTITUTIONAL COURT ON THE RIGHT TO A DECENT STANDARD OF LIVING
Keywords: dreptul la un nivel de trai decent; calitatea vieții